ESTIMASI KEGIATAN ALIH MUAT PADA KAPAL RAWAI TUNA BERDASARKAN DATA VMS DAN KOMPOSISI HASIL TANGKAPAN (Transshipment Activites Estimation in Tuna Longliner Base on VMS Data and Catch Composition) - Purnama, Rahman Hakim; Diniah, .; Wahju, Ronny I (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2016)
ABSTRACTTransshipment in longline fisheries is a common activity  at Nizam Zachman Jakarta  fishing port.  Publication  of  PERMEN  KP  No.  57  of  2014  causing  strong  protests  among  actors  and unloading included in PPS over Nizam Zahman.  The purpose of this research  are  to identify the movement patterns of longline vessels through VMS data  and to  estimate longline target catch by transshipment. This research was applied descriptive method.   Primary data was derived from the VMS tracking data and interviews. Secondary data were obtained from 276 loading and unloading activities longline tuna catches. The results of this study indicated that the movement of the ship only  accommodate  the  catch  can  be  clearly  identified  by  VMS.  Transshipment  activity,  mostly happened  to target catches which  reaching  62% with bigeye tunadominantly  92.61%. On bycatch, there  were three  dominant  species,  that  were  mackerel scad,  mackerel tuna  and southern bluefin tuna. Fresh conditions dominate activity over the load by 89%, ie 46% of the quality of export  whole quality and 43% reject  quality. Fresh condition consists of six species, bigeye tuna (2,408,999 kg), yellowfin tuna (970,186 kg), Swordfish (47,774 Kg), southern bluefin tuna (4,435 kg), marlin (962 kg)  and  albacore  (39  kg).  Transshipment  at  Nizam  Zachman  Jakarta  fishing  port  dominated  by fishing vessel measured 61-100 GT and < 50 days long trip.  It  shows that there was correlation between transshipment activity and fresh tuna industry.Keywords: catch composition, transshipment, tuna longline, VMS dataABSTRAKAlih muat hasil tangkapan dalam perikanan  longline  umum terjadi di PPS Nizam Zachman Jakarta. Terbitnya PERMEN KP No 57 tahun 2014 menimbulkan protes keras di kalangan pelaku alih  muat  termasuk  di  PPS  Nizam  Zahman.   Tujuan  dari  penelitian  ini  yaitu  menganalisis  pola pergerakan  kapal  perikanan  dalam  melakukan  kegiatan  alih  muat  dan  mengestimasi  komposisi hasil  tangkapan  rawai  tuna  melalui  kegiatan  alih  muat.  Penelitian  ini  menggunakan  metode deskriptif.  Data  primer  berasal  dari  data  tracking  VMS  dan  hasil  wawancara.  Data  sekunder diperoleh  dari  276  aktivitas  bongkar  muat  hasil  tangkapan  rawai  tuna.  Hasil  penelitian  ini menunjukkan  bahwa  pergerakan  kapal  yang  hanya  menampung  hasil  tangkapan  dapat teridentifikasi dengan jelas melalui VMS.  Kegiatan alih muat pada rawai tuna dominan terjadi pada hasil  tangkapan  utama  mencapai  62%  dengan  spesies  yang  dominan  yaitu  tuna  mata  besar dengan  prosentase  sebesar  92,61%.  Pada  hasil  tangkapan  sampingan  terdapat  3  spesies dominan yaitu layang, sunglir dan tuna sirip biru selatan. Kondisi segar mendominasi kegiatan alih muat sebesar 89%, yaitu 46% mutu kualitas ekspor utuh dan 43% mutu  reject. Kondisi segar terdiri atas  6  spesies,  yaitu  tuna  mata  besar  (2.408.999  kg),  madidihang  (970.186  kg),  ikan  pedang(47.774 Kg), tuna sirip biru selatan (4.435 kg), setuhuk (962 kg) dan albakora (39 kg). Produksi alih muat  didominasi  oleh  kapal  berukuran  61-100  GT  dan  lama  trip